PERANCANGAN DAN PENGUJIAN ALAT SENSOR PH SERTA SUHU BERBASIS INTERNET OF THINGS UNTUK MONITORING LIMBAH INDUSTRI TAHU - Pinandhita, Aqli Supremadi Naufal; Shobirin, Rizky Arief; Shalahuddin, Yanu; Srikalimah, Srikalimah (Universitas Muhammadiyah Ponorogo, 2023)
Tofu wastewater has negative impact on the river ecosystems and local residents because its smell and acidity. Therefore, this research aimed to design tools and test pH and temperature sensors based on Internet of Things (IoT) for monitoring the results of the installation of tofu waste wastewater treatment (WWTP) system in real time as wastewater quality monitoring system development thus it capable for wastewater monitoring intensively. Methodology of this research was experimentally for designing monitoring tools, which at tool design stage using an ESP 8266 microcontroller, pH4502c and DS18B20 as pH and temperature sensors, respectively. And also, it was communicated with Arduino IDE and Blynk software to create program code on the microcontroller and as monitoring on the computer server and smartphones, respectively. The used statistical compatibility test was percentage error, validity and reliability tests based on the monitoring tool data response to observed its suitability of the wastewater monitoring tool set for sustainability in home industries. In the %error test, there were results in reading values by the pH and temperature sensor of 0.92-1.45% in the tofu waste and whole neutralization, coagulation, sedimentation and filtration compartments; however, there was %error result of 0.92-7.31% on the pH sensor for the tofu wastewater tub. There were very valid and reliable results on tofu waste and whole compartments of the WWTP. Based on these results, the wastewater monitoring tools set was declared suitable for continuous use in the tofu industry with recommendations for routine calibration at least every 3 days of use.